Queer globalizations: citizenship and the afterlife of colonialism - Cruz, Arnaldo; Manalansan, Martin F. (New York University Press, 2002)
Globalization has a taste for queer cultures. Whether in advertising, film, performance art, the internet, or in the political discourses of human rights in emerging democracies, queerness sells and the transnational circulation of peoples, identities and social movements that we call "globalization" can be liberating to the extent that it incorporates queer lives and cultures. From this perspective, globalization is seen as allowing the emergence of queer identities and cultures on a global scale. The essays in Queer Globalizations bring together scholars of postcolonial and lesbian and gay studies in order to examine from multiple perspectives the narratives that have sought to define globalization. In examining the tales that have been spun about globalization, these scholars have tried not only to assess the validity of the claims made for globalization, they have also attempted to identify the tactics and rhetorical strategies through which these claims and through which global circulation are constructed and operate.
Section: vii, 274 p. ; 24 cm.
Keywords: 1900-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; cours; discipline; discours dominant; histoire et politique; hétéronormativité; hétérosexisme; identités LGBTQIA2+; premier cycle; périodes historiques; queer; racisme; régions géographiques; sexualité; shm4000; système colonial; systèmes d'oppressions; thématiques; états-unis

Miroir bisexuel: une socio-anthropologie de l'invisible - Deschamps, Catherine (Balland, 2002)
Les bisexuels, ça n'existe pas ! ". A-t-on déjà entendu proférer de tels propos sur les noirs, les blancs, les juifs, les femmes ou les gays ? Étrange démarche que de produire du sens au sujet d'une population dont la présence même est mise en doute. Mais la demande de preuve adressée aux femmes et aux hommes bisexuels a pour leurs émetteurs une fonction : les protéger des doutes identitaires qu'ils suscitent. Fondé sur l'observation de la seule association bisexuelle française ayant pignon sur rue, le présent ouvrage met l'accent en priorité sur les caractéristiques identitaires, politiques et culturelles. La bisexualité apparaît alors comme le terrain d'observation privilégié de l'ensemble des orientations sexuelles. Elle permet de la sorte une déconstruction des normes les plus insidieuses, communes à toutes et à tous. Car la bisexualité, plus une identité pertinente en elle-même, est une délatrice de l'invisible, qui ouvre, non plus à une approche diffractée de la différence, mais à une compréhension holistique du phénomène des sexualités.
Section: 299 pages
Keywords: 1900-1999; LGBTQIA2+; approches et analyses; corps; cours; discipline; discours dominant; europe; france; histoire et politique; hétérosexisme; identités LGBTQIA2+; premier cycle; périodes historiques; queer; régions géographiques; sexualité; shm4000; systèmes d'oppressions; thématiques

Le mouvement gai et lesbien américain face au SIDA - Marche, Guillaume (L'Homme & la Société, 2002)
Divided between essentialism and constructivism, the mobilization of united-statesian homosexuals becomes a real social movement when it goes beyond the opposition between integrationism and differentialism. Thanks to a complex identity forged by ACT-UP, it has been able in this way to resist AIDS. A comparison between San Francisco and New York shows that the initiative comes from the bottom up. Collective action is most effective as it takes account of differences (such as ethnicity) between homosexuals. This requirement has been dictated by the evolution of AIDS since the 1990s. It is, therefore, in stressing the subjectivity of the actors that the gay and lesbian movement can continue and contribute to social change in the United States.
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; cours; discipline; discours dominant; histoire et politique; homophobie; hétérosexisme; identités LGBTQIA2+; lesbianisme; premier cycle; périodes historiques; queer; régions géographiques; santé; sexualité; shm4000; systèmes d'oppressions; thématiques; états-unis

Sexualities : Sexualities and their futures - Plummer, Kenneth (Routledge, 2002)
Bringing together classic writings on sexuality from a social science perspective, this fascinating set covers topics including the history of the study of the area, theoretical approaches and issues of gender and sexuality. Volume four considers the wider issues around sexualities - addressing social change, postmodernity and the shifting of sexualities, and presenting an examination of the term 'queer'. An epilogue of suggested further reading is also included.
Keywords: approches et analyses; discipline; genre; postmodernisme; queer; sciences humaines; sexualité; sociologie; thématiques